Aldol condensation reaction method, catalytic material and preparation

By using zirconium silicon molecular sieve catalyst, the aldol condensation reaction between methyl acetate and formaldehyde was catalyzed, and the problem of insufficient conversion rate and selectivity in the prior art was solved, and a catalytic effect with high activity and high selectivity was achieved.

CN119528726APending Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311112116.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when preparing methyl acrylate by aldol condensation reaction of methyl acetate and formaldehyde, the conversion rate and selectivity are insufficient, and the catalyst activity and reusability are poor.

Method used

Zirconium silicon molecular sieve is used as a catalyst, which consists of zirconium, silicon, oxygen and alkali metal elements. The center value of its Zr 3d5/2 zirconium spectrum peak binding energy is characterized by XPS at 182.4±0.4eV. It is mixed with hydroxide or salt of alkali metal and prepared after drying and calcining.

Benefits of technology

The conversion rate of methyl acetate and the selectivity of methyl acrylate are significantly improved, while the activity and reusability of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to an aldol condensation method, which is characterized in that in the presence of a catalyst, a carbonyl-containing compound with alpha-H and another carbonyl-containing compound are subjected to a carbon-carbon bond coupling reaction to generate a carbonyl-containing compound with beta-hydroxyl or a carbonyl-containing compound with alpha, beta-unsaturated bonds, the catalyst is a zirconium-silicon molecular sieve or a catalytic material containing the zirconium-silicon molecular sieve, the zirconium-silicon molecular sieve contains zirconium, silicon, oxygen and alkali metal elements, the zirconium-silicon molecular sieve is represented by XPS, the central value of zirconium spectrum peak binding energy of Zr 3d5 / 2 is 182.4 + / -0.4 eV, the zirconium-silicon molecular sieve is represented by pyridine infrared, the acid content at 150 DEG C of the zirconium-silicon molecular sieve is less than 40 [mu] mol / g, and the acid content at 150 DEG C of the zirconium-silicon molecular sieve is less than 40 [mu] mol / g. And the acid content at 50 DEG C is less than 200 [mu] mol / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of an organic reaction catalytic method and related catalysts, and more specifically to an aldol condensation catalytic reaction method and the molecular sieve catalyst used and the preparation thereof. Background Art

[0002] Methyl acrylate is an important organic intermediate and is widely used in rubber, leather, medicine, coatings and other industries. There are currently several main methods for producing methyl acrylate. Industrial production is mainly based on propylene oxidation, which has excellent technical and economic advantages but low efficiency. The acrylonitrile hydrolysis method has a small output and sulfuric acid cannot be recycled. The propane oxidation method is a commonly used method. Although it is cheap, the product yield is low. The propylene oxidation method and the acrylonitrile hydrolysis method are highly dependent on petroleum. The preparation of methyl acrylate by the condensation reaction of coal-based methyl acetate (or acetic acid) and formaldehyde is a very important and highly productive process synthesis route. It not only has low production costs, but also effectively controls the discharge of polluted waste liquid, and has great application prospects.

[0003] The literature (Chemical Industry Progress, 2021, 40(4): 2005-2015) reported the research progress of the route of acetic acid (ester)-formaldehyde condensation to acrylic acid (ester). The catalysts currently used in this route include VPO catalysts, alkali metal / alkaline earth metal catalysts and ionic liquid catalysts. Among them, VPO catalysts have high catalytic efficiency, but many side reactions and are easily deactivated; alkali metal / alkaline earth metal catalysts have no oxidative by-products and higher selectivity compared to VPO, but their catalytic efficiency is slightly lower; ionic liquid catalysts have mild reaction conditions and high selectivity, but product separation is difficult and the catalyst is difficult to reuse.

[0004] CN106693941A reported that Li, Na, K, Rb, Cs, Mg, Ca, Sr, and Ba were active components, the carrier was Al2O3 prepared by a coprecipitation method, the optimal catalyst was used, and the molar ratio of methyl acetate: formaldehyde: methanol was 1:2:2, the conversion rate of methyl acetate was 34.4%, and the selectivity of methyl acrylate was 93.4%.

[0005] CN104258901A discloses a Cs-loaded pure silicon molecular sieve catalyst, which uses KIT-6 as a carrier and different contents of Cs as an active component. The catalyst is applied to the reaction of preparing methyl acrylate by aldol condensation of methyl acetate and formaldehyde. When the molar ratio of the reaction raw materials methyl acetate, formaldehyde and methanol is 1:2:2, the conversion rate of methyl acetate can reach up to 35%, and the selectivity of methyl acrylate can reach up to 94%.

[0006] Teng He et al. reported in Catalysis Letters, 2019, 149(2):373-389 that cesium-loaded SiO2 was used as a catalyst and different contents of Cs as an active component in the reaction of methyl acetate and formaldehyde aldol condensation to prepare methyl acrylate. The molar ratio of the reaction raw materials methyl acetate, formaldehyde, and methanol was 1:2:2, the reaction temperature was 390°C, the conversion rate of methyl acetate was about 35%, and the selectivity of methyl acrylate was 85-90%.

[0007] Studies have shown that among various catalysts for catalyzing the aldol condensation reaction of methyl acetate and formaldehyde to prepare methyl acrylate, the performance of silica-supported Cs alkali metal catalyst is the best, but the catalyst activity is not ideal. In general, the selectivity of the target product of the aldol condensation reaction is not ideal. Summary of the invention

[0008] One of the objects of the present invention is to provide an aldol condensation reaction method with higher conversion rate and target product selectivity.

[0009] A second object of the present invention is to provide a catalytic material with high activity and selectivity.

[0010] A third object of the present invention is to provide a method for preparing a catalytic material.

[0011] In order to achieve one of the above-mentioned purposes, the present invention provides a method for aldol condensation in the first aspect, characterized in that, in the presence of a catalyst, a carbonyl-containing compound having α-H undergoes a carbon-carbon bond coupling reaction with another carbonyl-containing compound to generate a carbonyl-containing compound having β-hydroxyl or a carbonyl-containing compound having α,β-unsaturated bonds; the catalyst comprises a zirconium silicon molecular sieve, the zirconium silicon molecular sieve contains zirconium, silicon, oxygen and alkali metal elements, and the zirconium silicon molecular sieve is characterized by XPS, and its Zr 3d 5 / 2 The central value of the zirconium spectrum peak binding energy is located at 182.4±0.4eV.

[0012] In order to achieve the second objective, the present invention provides a catalytic material in a second aspect, characterized in that the catalytic material is a titanium silicon molecular sieve containing zirconium, silicon, oxygen and alkali metal elements, and the zirconium silicon molecular sieve is characterized by XPS. 5 / 2 The central value of the zirconium spectrum peak binding energy is located at 182.4±0.4eV.

[0013] In order to achieve the third of the above-mentioned purposes, the third aspect of the present invention provides a method for preparing zirconium silicon molecular sieve, characterized in that the zirconium silicon molecular sieve as a raw material is mixed with an alkali metal hydroxide or salt in the presence of an optionally added solvent, and then dried and calcined; the mixing treatment method adopts one or more of an impregnation method, an ion exchange method, a spraying method, a solid phase ion exchange method, and a grinding method, among which the preferred mixing treatment method is the grinding method.

[0014] Compared with the prior art, the advantages of the present invention are:

[0015] The zirconium silicon molecular sieve provided by the present invention has alkali metal and zirconium as main active components, the alkali metal provides alkaline active center, and zirconium provides acidic active center. Appropriate catalytic active center is generated through the interaction between alkali metal and zirconium, and the activity is improved and good selectivity is guaranteed in the aldol condensation reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the XPS spectrum of the molecular sieve comparison sample of Comparative Example 2.

[0017] Figure 2 This is the pyridine infrared spectrum of the molecular sieve comparison sample of Comparative Example 2.

[0018] Figure 3 This is the XPS spectrum of the molecular sieve sample of Example 1.

[0019] Figure 4 This is the pyridine infrared spectrum of the molecular sieve sample of Example 1. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] The present invention provides a catalytic material, characterized in that the catalytic material is a titanium silicon molecular sieve, containing zirconium, silicon, oxygen and alkali metal elements, and the zirconium silicon molecular sieve is characterized by XPS. 5 / 2 The central value of the binding energy of the zirconium spectrum peak is located at 182.4±0.4 eV, preferably 182.4±0.3 eV, more preferably 182.4±0.2 eV, and further preferably 182.4±0.1 eV.

[0022] XPS (X-ray photoelectron spectroscopy) characterization is based on the principle of photoelectron migration of atomic orbitals such as Zr (3d) and Si (2p), and can provide the composition and valence state of atoms with a thickness of 4 to 5 nm on the surface of the molecular sieve (Spectroscopy and Spectral Analysis, 2015, 35(12): 3514-3518). In general, depending on the structure and synthesis method of the molecular sieve, the Zr (3d 5 / 2 ) element's spectral peak binding energy center value is located at 182.8-183.7eV. The reduction of zirconium's electron binding energy indicates that its extranuclear electron cloud density is reduced, and there is a strong interaction with alkali metals. The catalytic material of the present invention is zirconium silicon molecular sieve, and its zirconium species binding energy is significantly lower than the binding energy of metal species in conventional zirconium silicon molecular sieve, and its performance is better than conventional zirconium silicon molecular sieve. In the present invention, the XPS characterization test method for zirconium silicon molecular sieve is a conventional method in the art.

[0023] In the catalytic material of the present invention, the alkali metal element is selected from one or more of lithium, sodium, potassium, rubidium, and cesium, preferably one or more of potassium, rubidium, and cesium, more preferably one or more of rubidium and cesium, and further preferably cesium. The alkali metal element of the present invention is uniformly dispersed in the zirconium silicon molecular sieve.

[0024] The catalytic material of the present invention has a molar ratio of the alkali metal element to the silicon element in the zirconium silicon molecular sieve of (0.001-0.1):1, preferably (0.005-0.08):1, more preferably (0.005-0.06):1, more preferably (0.008-0.05):1, and more preferably (0.01-0.03):1. The catalytic material of the present invention has a molar ratio of zirconium to silicon element of (0.001-0.05):1, preferably (0.004-0.03):1, more preferably (0.006-0.02):1, and more preferably (0.008-0.015):1. The molar ratio of each element in the molecular sieve is obtained by X-ray fluorescence spectrometer analysis method (XRF).

[0025] The catalytic material of the present invention, the zirconium silicon molecular sieve, its framework structure type in principle includes any suitable structure type or any suitable combination of structure types. Therefore, the available molecular sieve structure types in principle include the following structure types: ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFY, AHT, ANA, APC, APD, AST, ASV, AFX, ATN, ATO, ATS, ATT, ATV, AWO, AWW, BCT, BEA, BEC, BIK, BOF, BOG, BOZ, BPH, BRE, BSV, CAN, CAS, CDO, CFI, CGF, SCO, CFI, SGF, CGS, CHA, CHI, CLO, CON, CZ P, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EWT, EON, EPI, ERI, ESV, ETR, EUO, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IHW, ISV, ITE, I TH, ITW, IWR, IWW, IWV, JBW, JNT, JOZ, JRY, JSN, JSR, JST, JSW, KFI, LAU, LEV, LIO, LIT, LOS, LOV, LTA, LTF, LTJ, LTL, LTN, MAR, MAZ, MEI, MEL, M EP, MER, MFI, MFS, MON, MOR, MOZ, MRT, MSE, MSO, MTF, MTN, MTT, MTW, MVY, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OKO, OSI, OSO, OWE, PAR, PAU, PCR, PHI, PON, POR, POS, PSI, PTY, PUN, PWN, PWO, PWW, RHO, RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAF, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFS, SFW, SGT, SIV, SOD, SOF, SOR, SOS, SOV, SSF, SSY, STF, STI, STT, STW, SVR, SVV, SWY, SYT, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, WEN, YFI, YUG, ZON, and hybrid structures consisting of two or more of these structure types.Alternatively, it may be an amorphous structure such as MCM-41, MCM-48, SBA-15, etc. Further, MFI, MEL, and BEA structures are preferred.

[0026] The catalytic material of the present invention can be a zirconium silicon molecular sieve with a multi-level pore structure, which can be formed by direct synthesis or by post-treatment. For example, it can be synthesized by soft and hard template synthesis methods (silanization method, cellulose method, carbon black method, etc.), and expanded by acid and alkali treatment (for example, by hydrochloric acid, hydrofluoric acid, ammonium bifluoride, ammonium fluoride, sodium hydroxide, potassium hydroxide, ammonia water, ammonium carbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, etc.). The molecular sieve with a multi-level pore structure can be a molecular sieve containing micropores and at least one mesopore and / or macropore. The micropore diameter is less than 2nm, the mesopore diameter is 2-50nm, and the macropore diameter is greater than 50nm.

[0027] The catalytic material of the present invention is characterized by pyridine infrared acidity, and it can be found that the zirconium silicon molecular sieve has no obvious B acid and is mainly L acid. The acid amount at 150°C is less than 40μmol / g, preferably 35μmol / g, further preferably 30μmol / g, more preferably 25μmol / g, and more preferably 20μmol / g; the acid amount at 50°C is less than 200μmol / g, preferably 160μmol / g, further preferably 130μmol / g, and more preferably 100μmol / g. The pyridine infrared method is a conventional method for characterizing the acid amount of the catalyst. Through the adsorption of pyridine on the catalyst B acid and L acid, different vibrations are produced under the infrared spectrum, which can be used for quantitative characterization of the acid amount. Conventional pyridine infrared characterization measures the acid amount of the sample under temperature conditions of 200°C and above. Since the molecular sieve of the present invention has a small acid amount, it needs to be measured at a lower temperature.

[0028] The catalytic material of the present invention is characterized by NMR silicon spectrum, and it can be found that the zirconium silicon molecular sieve, Q 4 With Q 3 The ratio of the signal peak height is greater than 100, preferably greater than 150, further preferably greater than 200, more preferably greater than 250, further preferably greater than 300, and most preferably no Q 3 Signal peaks appear. In the NMR silicon spectrum, Q 4 (-113ppm) represents Si(OSi)4 species, Q 3 (-103ppm) represents Si(OSi)3(OH) species. The catalytic material zirconium silicon molecular sieve of the present invention has a low Q 3 The signal intensity of silicon species indicates that the zirconium silicon molecular sieve has fewer defect sites, more evenly dispersed active centers, and is more conducive to catalytic reactions.

[0029] The present invention also provides a method for preparing the above-mentioned catalytic material, characterized in that the zirconium silicon molecular sieve as a raw material is mixed with the hydroxide or salt of an alkali metal in the presence of an optionally added solvent, and then dried and calcined; the mixing treatment method adopts one or more of an impregnation method, an ion exchange method, a spraying method, a solid phase ion exchange method, and a grinding method, among which the preferred mixing treatment method is the grinding method.

[0030] In the preparation method of the present invention, the mixing treatment can be one or more of an impregnation method, an ion exchange method, a spraying method, a solid phase ion exchange method, and a grinding method, and can be repeated multiple times. Compared with other methods, the grinding method can make the alkali metal and the zirconium silicon molecular sieve contact better, and a grinding chemical reaction occurs, which is more conducive to the formation and uniform dispersion of catalytic active centers, so the grinding method is preferably used.

[0031] In the preparation method of the present invention, the zirconium silicon molecular sieve as a raw material can be obtained by a hydrothermal synthesis method or a post-synthesis method. Among them, the post-synthesis method can be a rearrangement method, a silicon aluminum molecular sieve dealuminization zirconium insertion method, a silicon boron molecular sieve deboronization zirconium insertion method, a silicon germanium molecular sieve degermaniumization zirconium insertion method, etc., and can be a liquid phase zirconium insertion method or a gas phase zirconium insertion method, and the present invention has no particular limitation. Preferably, the zirconium silicon molecular sieve as a raw material is obtained by a hydrothermal synthesis method.

[0032] In the preparation method of the present invention, the zirconium-silicon molecular sieve used as raw material has a molar ratio of zirconium to silicon of (0.001-0.05):1, preferably (0.004-0.03):1, further preferably (0.006-0.02):1, and more preferably (0.008-0.015):1.

[0033] In the preparation method of the present invention, the skeleton structure of the zirconium silicon molecular sieve as a raw material is preferably selected from a crystal structure, such as a crystal structure including MFI, MEL, MWW, BEA, MOR, SVR, etc., or one or more amorphous structures, wherein the amorphous structure includes MCM-41, MCM-48, SBA-15, etc. Preferably, one or more crystal structures are selected from MFI, MEL, and BEA, and more preferably, one or more crystal structures are selected from MFI and MEL having multi-level pore characteristics.

[0034] In the preparation method of the present invention, the alkali metal is selected from one or more of lithium, sodium, potassium, rubidium and cesium. Preferably, it is one or more of potassium, rubidium and cesium, more preferably one or more of rubidium and cesium, and further preferably cesium. The alkali metal element of the present invention is in a uniformly dispersed state in the catalyst.

[0035] The preparation method of the present invention, the alkali metal salt includes hydrochloride, hypochlorite, chlorite, metachlorate, perchlorate, nitrate, sulfate, hydrogen sulfate, sulfite, hydrogen sulfite, phosphate, hydrogen phosphate, dihydrogen phosphate, high phosphate, metaphosphate, phosphite, hypophosphite, carboxylate, pyrophosphate, ammonium salt, C1-C 20 The preferred alkali metal salt is a nitrate, carbonate, or hydroxide of an alkali metal. More specifically, the alkali metal hydroxide is cesium hydroxide, and the alkali metal salt is one or more of cesium nitrate, cesium carbonate, cesium bicarbonate, and cesium acetate.

[0036] In the preparation method of the present invention, the molar ratio of the alkali metal element to the silicon element in the zirconium silicon molecular sieve is (0.001-0.1):1, preferably (0.005-0.08):1, further preferably (0.005-0.06):1, more preferably (0.008-0.05):1, and most preferably (0.01-0.03):1.

[0037] In the preparation method of the present invention, the solvent can be an inorganic solvent or an organic solvent. The inorganic solvent includes water. The organic solvent is selected from C1-C 10 Alcohol, C3-C 10 Ketone, C2-C 10 The ester may be an aliphatic solvent or an aromatic solvent. The organic solvent may be a chlorinated solvent, such as one or more of chloroform, dichloromethane, chloroform, carbon tetrachloride, chloroethane, dichloroethane, chloroethane, and tetrachloroethane. The preferred organic solvent is an alcohol, and its typical alcohol is selected from C1-C6 alkanols, such as methanol, ethanol, propanol, and isopropanol, preferably methanol. The alkali metal is added as a salt solution in alcohol, and a low level of water may be contained in the solution, typically up to 50 vol%. The amount of the inorganic solvent or organic solvent added is calculated according to the carrier. Preferably, the solvent is preferably at least one of water, methanol, ethanol, propanol, chloroform, dichloromethane, and chloroform. The molar ratio of the zirconium silicon molecular sieve (calculated as SiO2) as a raw material to the solvent is preferably 1: (0-10), more preferably 1: (1-8), more preferably 1: (1.5-6), and more preferably 1: (1.5-4).

[0038] In the preparation method of the present invention, the temperature, time, pressure and other conditions are such that the alkali metal is allowed to contact the zirconium silicon molecular sieve as a raw material to form the XPS Zr 3d 5 / 2The catalytic material has zirconium spectrum characteristics, NMR silicon spectrum characterization characteristics and pyridine infrared acidity characterization. The preparation method of the present invention, the mixing treatment is carried out at 20-150°C, preferably 25-100°C, more preferably 30-70°C, and the pressure (absolute pressure) is 10-100KPa, preferably 20-80KPa, more preferably 30-50KPa for 5-120min, preferably 5-60min, and further preferably 10-30min. The mixing treatment is carried out under a certain vacuum degree, which is more conducive to the dispersion of alkali metals in zirconium silicon molecular sieves and forms a better interaction between zirconium and alkali metals. The contact treatment process can be carried out on equipment that meets the processing requirements, such as a vacuum glove box or a ball mill with vacuum.

[0039] The preparation method of the present invention also has a step of removing the solvent before drying, which can be pressure evaporation, normal pressure evaporation, reduced pressure evaporation, filtration, centrifugation, sedimentation, etc., and the present invention has no particular limitation. The drying is preferably carried out at a temperature range of 60-150°C, more preferably 90-140°C, and more preferably 100-130°C. The drying time is preferably 0.5-24h, more preferably 1-12h, and more preferably in the range of 2-6h. The calcination is preferably treated at 250-700°C for 0.5-24h, preferably 350-550°C for 1-12h. The calcination atmosphere is preferably an oxygen-containing atmosphere, and more preferably an air atmosphere; the calcination temperature is determined according to the decomposition temperature of the alkali metal element precursor, but the calcination temperature is preferably less than 550°C to prevent the alkali element precursor from decomposing. The calcination temperature is more preferably 400-500°C; in order to prevent a large change in the carrier structure or specific surface area, the calcination time is more preferably 3-8h.

[0040] The preparation method of the present invention also includes the step of obtaining a multi-level pore molecular sieve with the participation of a silane compound, such as N-phenyl-3-aminopropyltrimethoxysilane.

[0041] The present invention further provides a catalyst, which includes the zirconium silicon molecular sieve of the present invention, that is, the zirconium silicon molecular sieve contains zirconium, silicon, oxygen and alkali metal elements. The zirconium silicon molecular sieve is characterized by XPS. 5 / 2 The central value of the zirconium spectrum peak binding energy is located at 182.4±0.4 eV, and the weight ratio of the zirconium silicon molecular sieve to the catalyst is 5%-100%.

[0042] The present invention also provides a method for aldol condensation based on the above-mentioned catalytic materials and catalysts, characterized in that, in the presence of a catalyst, a carbonyl compound having α-H undergoes a carbon-carbon bond coupling reaction with another carbonyl compound to generate a carbonyl compound having β-hydroxyl or a carbonyl compound having α,β-unsaturated bonds; the catalyst comprises a zirconium silicon molecular sieve, which contains zirconium, silicon, oxygen and alkali metal elements, and the zirconium silicon molecular sieve is characterized by XPS, and its Zr 3d 5 / 2 The central value of the zirconium spectrum peak binding energy is located at 182.4±0.4eV.

[0043] In the aldol condensation method, the α and β positions refer to the functional groups of hydrocarbon molecules, such as carbonyl, hydroxyl, carboxyl, etc., and the carbon atoms of the first ortho and second ortho positions. The carbonyl-containing compound includes the first carbonyl compound and the second carbonyl compound, and the number of carbon atoms is preferably C1-C 20 The carbonyl compound may include the following structure:

[0044] C1-C 12 Alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl; preferably C1-C6 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, and particularly preferably C1-C4 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isohexyl, sec-butyl and tert-butyl.

[0045] C3-C 12 Cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; preferably cyclopentyl, cyclohexyl and cycloheptyl.

[0046] Examples of substituted cycloalkyl groups are: 2-methylcyclopentyl, 3-methylcyclopentyl, 2-methylcyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2-methoxycyclopentyl, 2-chlorocyclopentyl, 2-methylthiocyclohexyl and other derivatives.

[0047] C7-C 13 Arylalkyl, preferably C7-C 12 Phenylalkyl, such as benzyl, 1-phenylethyl, 2-phenylethyl, 1-phenylpropyl, 2-phenylpropyl, 3-phenylpropyl, 1-phenylbutyl, 2-phenylbutyl, 3-phenylbutyl and 4-phenylbutyl, particularly preferably benzyl;

[0048] C6-C 14 Aryl, for example phenyl, 1-naphthyl, 2-naphthyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthrenyl, 2-phenanthrenyl, 3-phenanthrenyl, 4-phenanthrenyl, 9-phenanthrenyl, preferably phenyl, which is unsubstituted or substituted with one or more of the following groups:

[0049] C1-C 12 Alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl; preferably C1-C6 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, and particularly preferably C1-C4 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isohexyl, sec-butyl and tert-butyl.

[0050] Halogen, such as fluorine, chlorine, bromine, iodine, preferably chlorine.

[0051] C1-C 12 Alkoxy, preferably C1-C6 alkoxy, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentylpropoxy, n-hexyloxy and isohexyloxy, particularly preferably methoxy, ethoxy, n-propoxy, n-butoxy.

[0052] In the aldol condensation method, preferably, the first carbonyl compound contains α-H, and the second carbonyl compound contains α-H or does not contain α-H. Further preferably, the carbonyl compound not containing α-H is formaldehyde, benzaldehyde, furfural, 5-hydroxymethylfurfural, 5-methylfurfural or a derivative thereof, more preferably formaldehyde; the carbonyl compound containing α-H is at least one of acetaldehyde, propionaldehyde, acetone, butyraldehyde, butanone, valeraldehyde, pentanone, hexanal, hexanone, cyclohexanone, cyclopentanone, acetic acid, propionic acid, malonic acid, butyric acid, succinic acid, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, cyclohexyl acetate, methyl propionate, ethyl propionate, butyl propionate, dimethyl malonate, methyl butyrate, dimethyl succinate, ethyl butyrate or a derivative thereof.

[0053] In the aldol condensation method, the reaction conditions are that the molar ratio of the second carbonyl compound to the first carbonyl compound is 1:(0.1-10), preferably 1:(0.2-6), further preferably 1:(0.4-4), more preferably 1:(0.8-3), and most preferably 1:(1-2.5).

[0054] In the aldol condensation method, the carbonyl compound mixed stream may further include one or more diluents, the diluents include at least one of alcohols, ethers, alkanes, halogenated alkanes, and toluene, preferably methanol, cycloalkane, ether, and toluene. The molar ratio of the diluent to the carbonyl compound is (30-0.5):1, preferably (20-0.7):1, further preferably (10-0.8):1, more preferably (5-0.9):1, and most preferably (4-1):1.

[0055] In the aldol condensation method, the reaction can be carried out in an atmosphere containing at least one of N2, He, Ar, CH4, C2H6, H2, CO, and CO2, preferably in an atmosphere containing N2. The reaction temperature is 260-500°C, preferably 300-480°C, and more preferably 320-400°C. Before the reaction, the temperature of the mixed solution is preferably raised to between 300-400°C, more preferably between 320-400°C. The reaction pressure (gauge pressure) is 0-2.0MPa, preferably 0.2-1.5MPa, and more preferably 0.5-1.5MPa. Based on the sum of the masses of the carbonyl compound and the diluent, the reaction liquid hourly space velocity is 0.05-5h -1 , preferably 0.08-3h -1 , more preferably 0.3-2.5h -1 .

[0056] The method of aldol condensation, more specifically, is the aldol condensation reaction of formaldehyde with methyl acetate or methyl propionate. Wherein, the formaldehyde source is an anhydrous formaldehyde source, preferably methylal, trioxymethylene and paraformaldehyde. The inventors have found that the use of the catalytic material provided by the present invention, i.e., zirconium silicon molecular sieve as a catalyst, can surprisingly greatly improve the activity and selectivity for the condensation of methylene sources such as formaldehyde with carboxylic acids or alkyl esters such as methyl acetate and methyl propionate to form olefinically unsaturated carboxylic acids.

[0057] Therefore, in a specific embodiment, the conditions for the aldol condensation reaction of formaldehyde and methyl acetate include: a molar ratio of methyl acetate to formaldehyde of 1:5 to 1:1, a molar ratio of methanol to methyl acetate of 1:1 to 2:1, a reaction temperature of 320 to 400°C, a reaction pressure (gauge pressure) of 0 to 1 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.3 to 2.5 h -1 In another specific embodiment, the conditions for the aldol condensation reaction of formaldehyde and methyl propionate include: a molar ratio of methyl propionate to formaldehyde of 1:2 to 1:0.2, a molar ratio of methanol to methyl propionate of 1:1 to 5:1, a reaction temperature of 320 to 400°C, a reaction pressure (gauge pressure) of 0 to 1 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.3 to 2.5 h -1The space velocity should be understood as the mass space velocity, which means the ratio of the mass flow rate of the total mass of the reactant substrate and the diluent (in units of (mass / time)) to the mass of the catalyst. Therefore, the unit of the space velocity is h -1 .

[0058] The method of the aldol condensation is preferably carried out in a fixed bed reactor, a fluidized bed reactor or an autoclave reactor. It will be appreciated by those skilled in the art that, depending on the different reactors used, the catalyst of the present invention can be the original powder of the zirconium silicon molecular sieve, or it can be a shaped catalyst after the zirconium silicon molecular sieve is shaped. The separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered skeleton molecular sieve is used as the catalyst, the separation of the product and the recycling of the catalyst can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation and the like. Alternatively, the catalyst can also be shaped and loaded into a fixed bed reactor, and the catalyst is recovered after the reaction is completed. The separation and recovery methods of various catalysts are often involved in the existing literature, which will not be described in detail here.

[0059] The present invention is described in detail below by way of examples, but the present invention is not limited thereto.

[0060] The XRF results of the samples were tested using a ZSX100E X-ray fluorescence spectrometer, produced by Rigaku, Japan. The test conditions were room temperature tableting, using tungsten-palladium, an excitation voltage of 40Kv, and an excitation current of 250mA.

[0061] The XPS characterization experiment instrument of the sample is an ESCALAB 250 X-ray photoelectron spectrometer produced by Thermo Fisher Scientific. The test conditions are monochromatic Al Kα X-ray, energy 1486.6 eV, power 150 W, and the C1s peak (284.8 eV) of contaminated carbon is used to correct the charge shift.

[0062] Sample 29 Si MAS NMR characterization experiments were performed on an AVANCEⅢ600WB NMR spectrometer, using a 7mm double resonance probe and a Ф4mm ZrO2 rotor, produced by Bruker. The test was conducted at room temperature with a resonance frequency of 99.3MHz, a magic angle speed of 5kHz, a pulse width of 2.73μs, a cycle delay time of 5.0s, a scan number of about 500 times, and a heavy water lock field.

[0063] The pyridine infrared absorption spectrum (Py-IR) of the sample was measured on the FTS3000 Fourier transform infrared spectrometer produced by BIO-RAD Company in the United States. The sample was pressed into a tablet and sealed in the in-situ cell of the infrared spectrometer. The sample was vacuumed to 10 -3Pa, maintain for 1 hour to desorb the gas molecules on the sample surface, and cool to room temperature. Introduce pyridine vapor with a pressure of 2.67 Pa into the in-situ cell, balance for 30 minutes, raise the temperature to 50°C, and evacuate to 10 -3 Pa, hold for 30 min, cool to room temperature, and -1 Scan within the wave number range and record the infrared absorption spectrum of pyridine adsorption at 50°C. Then move the sample in the infrared absorption cell to the heat treatment area, raise the temperature to 150°C, and evacuate to 10 -3 Pa, keep for 30 min, cool to room temperature, and record the infrared spectrum of pyridine adsorption at 150 °C. -1 The peak at 1540 cm is generated by the reaction between the L acid center and pyridine. -1 The peak is produced by the reaction of B acid and pyridine.

[0064] The catalytic performance test adopts a fixed-bed reactor at normal pressure, and the prepared catalyst is used to catalyze the aldol condensation of methyl acetate and formaldehyde to synthesize methyl acrylate. Among them, the molar ratio of methyl acetate to formaldehyde is 1:1, methanol is used as solvent, the molar ratio of methyl acetate to methanol is 1:2, the feed space velocity of the raw material mixture is 1h-1; the amount of catalyst is 5g; the carrier gas (N2) flow rate is maintained at 50mL / min during the reaction, and the reaction temperature is 360°C. The product is condensed and then subjected to chromatographic analysis. Unless otherwise specified, the raw materials in the examples of this application are purchased through commercial channels.

[0065] The analytical methods in the embodiments and comparative examples are as follows:

[0066] The composition of the reaction product was analyzed by gas chromatography, and the analysis results were quantified by external standard method. The chromatographic analysis conditions were: Agilent 6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 200°C at a rate of 15°C / min and maintained for 3 min. FID detector, detector temperature 300°C.

[0067] The conversion rate and selectivity in the embodiment are calculated as follows:

[0068]

[0069]

[0070] Comparative Example 1

[0071] Comparative Example 1 illustrates the preparation, characterization and evaluation of Cs / SiO2 catalyst.

[0072] Preparation of SiO2: Mix 100 mL of water and tetraethyl silicate at room temperature, add aqueous ammonia to the mixture dropwise until pH = 13, then stir at 30°C for 30 min, filter the hydrolyzed silicon dioxide, dry it in a drying oven at 110°C overnight, cool it to room temperature and grind it to obtain carrier amorphous silicon dioxide.

[0073] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then immerse SiO2 in the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of SiO2 (calculated as silicon dioxide) to solvent is 1:50. Immerse for 30 minutes at an absolute pressure of 100kPa and 30°C to make the cesium ions evenly distributed on the silicon dioxide. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / SiO2 catalyst, numbered D1. The characterization and evaluation results are shown in Table 1.

[0074] Comparative Example 2

[0075] Comparative Example 2 illustrates the preparation, characterization and evaluation of Zr-MFI molecular sieve.

[0076] Tetraethyl orthosilicate (TEOS), zirconium n-propoxide and tetrapropylammonium hydroxide (TPAOH, 25wt%) solution were mixed in a molar ratio of SiO2: 0.015ZrO2: 0.36TPAOH: 35H2O, and then stirred for 15 minutes to obtain a clear liquid. Finally, water was added to the clear liquid, stirred at 348-353K for about 3 hours to obtain a clear sol, and then crystallized at 443K for 3 days. After that, the obtained solid was filtered, washed with distilled water, dried at 373K for 5 hours, and then calcined at 823K for 5 hours to obtain the molecular sieve Zr-MFI, numbered D2. The characterization and evaluation results are shown in Table 1.

[0077] The XPS spectrum of D2 is shown in Figure 1 , pyridine infrared spectrum see Figure 2 .

[0078] Comparative Example 3

[0079] Comparative Example 3 illustrates the preparation, characterization and evaluation of Zr-MEL molecular sieve.

[0080] Tetraethyl orthosilicate (TEOS), zirconium n-propoxide and tetrabutylammonium hydroxide (TBAOH, 40wt%) solution were mixed in a molar ratio of SiO2: 0.01ZrO2: 0.36TBAOH: 35H2O, and then stirred for 15 minutes to obtain a clear liquid. Finally, water was added to the clear liquid, stirred at 348-353K for about 3 hours to obtain a clear sol, and then crystallized at 443K for 3 days. After that, the obtained solid was filtered, washed with distilled water, dried at 373K for 5 hours, and then calcined at 823K for 5 hours to obtain a molecular sieve Zr-MEL, numbered D3. The characterization and evaluation results are shown in Table 1.

[0081] Example 1

[0082] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then mix Zr-MFI with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of Zr-MFI (calculated as silicon dioxide) to solvent is 1:3. Grind the mixture for 30 minutes at an absolute pressure of 50 kPa and 30°C to make the cesium ions evenly distributed on Zr-MFI. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MFI catalyst, numbered CZ1. The characterization and evaluation results are shown in Table 1.

[0083] The XPS spectrum of CZ1 is shown in Figure 3 , pyridine infrared spectrum see Figure 4 .

[0084] Example 2

[0085] Weigh a certain amount of cesium nitrate and dissolve it in deionized water, then mix Zr-MFI with the cesium nitrate solution. Among them, the molar ratio of cesium to silicon is 0.04, and the molar ratio of Zr-MFI (calculated as silicon dioxide) to solvent is 1:8. Grind the mixture for 50 minutes at an absolute pressure of 100 kPa and 25°C to make the cesium ions evenly distributed on Zr-MFI. Then evaporate the solvent, dry it in a drying oven at 110°C for 3 hours, and calcine it in a muffle furnace at 450°C for 6 hours to obtain a Cs / Zr-MFI catalyst, numbered CZ2. The characterization and evaluation results are shown in Table 1.

[0086] Example 3

[0087] Weigh a certain amount of cesium hydroxide and dissolve it in isopropanol, then mix Zr-MFI with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.01, and the molar ratio of Zr-MFI (calculated as silicon dioxide) to solvent is 1:6. Grind the mixture for 60 minutes at an absolute pressure of 80 kPa and 70°C to make the cesium ions evenly distributed on Zr-MFI. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MFI catalyst, numbered CZ3. The characterization and evaluation results are shown in Table 1.

[0088] Example 4

[0089] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then mix Zr-MFI with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.015, and the molar ratio of Zr-MFI (calculated as silicon dioxide) to solvent is 1:2. Grind the mixture for 30 minutes at an absolute pressure of 30 kPa and 40°C to make the cesium ions evenly distributed on Zr-MFI. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 430°C for 6 hours to obtain a Cs / Zr-MFI catalyst, numbered CZ4. The characterization and evaluation results are shown in Table 1.

[0090] Example 5

[0091] Weigh a certain amount of cesium acetate and dissolve it in deionized water, then mix Zr-MFI with the cesium acetate solution. The molar ratio of cesium to silicon is 0.02, and the molar ratio of Zr-MFI (calculated as silicon dioxide) to solvent is 1:4. Grind the mixture for 10 minutes at an absolute pressure of 40 kPa and 60 ° C to make the cesium ions evenly distributed on Zr-MFI. Then evaporate the solvent, dry it in a drying oven at 110 ° C for 6 hours, and calcine it in a muffle furnace at 400 ° C for 6 hours to obtain a Cs / Zr-MFI catalyst, numbered CZ5. The characterization and evaluation results are shown in Table 1.

[0092] Example 6

[0093] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then mix Zr-MEL with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of Zr-MEL (calculated as silicon dioxide) to solvent is 1:3. Grind the mixture for 30 minutes at an absolute pressure of 50 kPa and 30°C to make the cesium ions evenly distributed on Zr-MEL. Then evaporate the solvent, dry it in a drying oven at 120°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MEL catalyst, numbered CZ6. The characterization and evaluation results are shown in Table 1.

[0094] Comparative Example 4

[0095] Comparative Example 4 illustrates the preparation and characterization of a zirconium silicon molecular sieve having a multi-level pore structure obtained with the participation of a silanization agent.

[0096] Tetraethyl orthosilicate (TEOS), zirconium n-propoxide and tetrapropylammonium hydroxide (TPAOH, 25wt%) solution were mixed in a molar ratio of SiO2: 0.015ZrO2: 0.36TPAOH: 35H2O, and then stirred for 15 minutes to obtain a clear liquid. Finally, water was added to the clear liquid, and stirred at 348-353K for about 3 hours to obtain a clear sol. Then a small amount of N-phenyl-3-aminopropyltrimethoxysilane was added, and then crystallized at 443K for 3 days. After that, the obtained solid was filtered, washed with distilled water, dried at 373K for 5 hours, and then calcined at 823K for 5 hours to obtain the molecular sieve Zr-MFI-PHA, numbered D4. The characterization and evaluation results are shown in Table 1.

[0097] Comparative Example 5

[0098] Comparative Example 5 illustrates the Cs / SBA-15 catalyst, preparation and characterization.

[0099] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then immerse the SBA-15 molecular sieve in the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of SiO2 (calculated as silicon dioxide) to solvent is 1:50. The immersion treatment is carried out at an absolute pressure of 100kPa and 30°C for 30 minutes to make the cesium ions evenly distributed on the SBA-15. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / SBA-15 catalyst, numbered D5. The characterization and evaluation results are shown in Table 1.

[0100] Example 7

[0101] Weigh a certain amount of cesium hydroxide and dissolve it in deionized water, then mix the sample D4 obtained in Comparative Example 4 with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of Zr-MFI-PHA (calculated as silicon dioxide) to the solvent is 1:3. Grind the mixture for 30 minutes at an absolute pressure of 50 kPa and 30°C to make the cesium ions evenly distributed on the Zr-MFI-PHA. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MFI-PHA catalyst, numbered CZ7. The characterization and evaluation results are shown in Table 1.

[0102] Example 8

[0103] Weigh a certain amount of cesium nitrate and dissolve it in deionized water, then mix the sample D4 obtained in Comparative Example 4 with the cesium nitrate solution. Among them, the molar ratio of cesium to silicon is 0.03, and the molar ratio of Zr-MFI-PHA (calculated as silicon dioxide) to the solvent is 1:2. Grind the mixture for 20 minutes at an absolute pressure of 50 kPa and 50°C to make the cesium ions evenly distributed on the Zr-MFI-PHA. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 450°C for 6 hours to obtain a Cs / Zr-MFI-PHA catalyst, numbered CZ8. The characterization and evaluation results are shown in Table 1.

[0104] Example 9

[0105] Weigh a certain amount of cesium hydroxide and dissolve it in anhydrous ethanol, then mix the sample D4 obtained in Comparative Example 4 with the cesium hydroxide solution. Among them, the molar ratio of cesium to silicon is 0.03, and the molar ratio of Zr-MFI-PHA (calculated as silicon dioxide) to the solvent is 1:3. Grind the mixture for 30 minutes at an absolute pressure of 40 kPa and 60°C to make the cesium ions evenly distributed on Zr-MFI-PHA. Then evaporate the solvent, dry it in a drying oven at 110°C for 6 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MFI-PHA catalyst, numbered CZ9. The characterization and evaluation results are shown in Table 1.

[0106] Example 10

[0107] Weigh a certain amount of cesium acetate and dissolve it in deionized water, then mix the sample D4 obtained in Comparative Example 4 with the cesium acetate solution. Among them, the molar ratio of cesium to silicon is 0.02, and the molar ratio of Zr-MFI-PHA (calculated as silica) to solvent is 1:4. Grind the mixture for 10 minutes at an absolute pressure of 30 kPa and 70°C to make the cesium ions evenly distributed on Zr-MFI-PHA. Then evaporate the solvent, dry it in a drying oven at 110°C for 3 hours, and calcine it in a muffle furnace at 400°C for 6 hours to obtain a Cs / Zr-MFI-PHA catalyst, numbered CZ10. The characterization and evaluation results are shown in Table 1.

[0108] Table 1

[0109]

[0110] From the comparison between Examples 1-10 and Comparative Examples 1-5 in Table 1, it can be seen that the zirconium silicon molecular sieve of the present invention:

[0111] (1) The binding energy of Zr element is 182.4-182.5eV, which is significantly lower than 183.3eV and 183.6eV of conventional zirconium silicon molecular sieves;

[0112] (2) The acid content at 50°C and 150°C is significantly lower than that of conventional zirconium silicate molecular sieves;

[0113] (3) No significant Q 3 Silicon NMR peak, therefore, has a good raw material conversion rate and target product selectivity, especially after pore expansion by silanization treatment (PHA), the catalytic performance is further improved.

[0114] It can also be seen from the comparison of Examples 1-10 and Comparative Examples 1-5 in Table 1 that the aldol condensation reaction method of Examples 1-10 of the present invention has a high conversion rate of methyl acetate and a high selectivity for methyl acrylate. According to GC-MS characterization analysis, the main product is methyl acrylate, and the main by-products are methacrolein, methyl methacrylate, etc., while the main product of Comparative Examples 1-5 is methyl acrylate, and the main by-products are acetone, acetic acid, etc.

Claims

1. A method for aldol condensation, characterized in that In the presence of a catalyst, a carbonyl compound having α-H undergoes a carbon-carbon bond coupling reaction with another carbonyl compound to generate a carbonyl compound having β-hydroxyl or a carbonyl compound having α,β-unsaturated bonds; the catalyst is a zirconium silicon molecular sieve or a catalytic material containing a zirconium silicon molecular sieve, the zirconium silicon molecular sieve contains zirconium, silicon, oxygen and alkali metal elements, and the zirconium silicon molecular sieve is characterized by XPS, and its Zr 3d 5 / 2 The central value of the binding energy of the zirconium spectrum peak is located at 182.4±0.4 eV. The zirconium silicon molecular sieve is characterized by pyridine infrared spectroscopy, and its acid content at 150°C is less than 40 μmol / g, and its acid content at 50°C is less than 200 μmol / g.

2. The method of aldol condensation according to claim 1, characterized in that The zirconium silicate molecular sieve was characterized by NMR silicon spectrum, Q 4 With Q 3 The ratio of the signal peak height is greater than 100, where Q 4 (-113ppm) represents Si(OSi)4 species, Q 3 (-103ppm) represents Si(OSi)3(OH) species.

3. The method of aldol condensation according to claim 2, characterized in that The Q 4 With Q 3 The ratio of the signal peak heights is greater than 150, preferably greater than 200, further preferably greater than 250, and more preferably greater than 300.

4. The method of aldol condensation according to claim 1, characterized in that The zirconium silicate molecular sieve was characterized by NMR silicon spectrum, and there was no Q 3 The signal peak appears, Q 3 (-103ppm) represents Si(OSi)3(OH) species.

5. The method of aldol condensation according to claim 1, characterized in that The alkali metal element is selected from one or more of lithium, sodium, potassium, rubidium and cesium.

6. The method of aldol condensation according to claim 1, characterized in that The molar ratio of the alkali metal element to the silicon element in the zirconium silicon molecular sieve is (0.001-0.1):1, preferably (0.005-0.08):1, further preferably (0.005-0.06):1, more preferably (0.008-0.05):1, and most preferably (0.01-0.03):

1.

7. The method of aldol condensation according to claim 1, characterized in that The zirconium-silicon molecular sieve has a molar ratio of zirconium to silicon of (0.001-0.05):1, preferably (0.004-0.03):1, further preferably (0.006-0.02):1, and more preferably (0.008-0.015):

1.

8. The method of aldol condensation according to claim 1, characterized in that The zirconium silicate molecular sieve has a skeleton structure selected from at least one crystalline structure including MFI, MEL, MWW, BEA, MOR, and SVR structure molecular sieves; or the zirconium silicate molecular sieve has an amorphous structure selected from at least one amorphous structure including MCM-41, MCM-48, and SBA-15 structure molecular sieves.

9. The method for aldol condensation according to claim 1, characterized in that The zirconium silicate molecular sieve has a multi-level pore structure, containing micropores and at least one mesopore and / or macropore. The micropore diameter is less than 2nm, the mesopore diameter is 2-50nm, and the macropore diameter is greater than 50nm.

10. The method for aldol condensation according to claim 1, characterized in that It is the aldol condensation reaction between formaldehyde and methyl acetate or formaldehyde and methyl propionate.

11. The method of aldol condensation according to claim 1, characterized in that The formaldehyde and methyl acetate undergo an aldol condensation reaction, and the conditions include: a molar ratio of methyl acetate to formaldehyde of 1:2 to 5:1, a molar ratio of methanol to methyl acetate of 1:1 to 2:1, a reaction temperature of 320 to 400°C, a reaction gauge pressure of 0 to 1 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.3 to 2.5 h -1 .

12. The method of aldol condensation according to claim 1, characterized in that The formaldehyde and methyl propionate undergo an aldol condensation reaction, and the conditions include: a molar ratio of methyl propionate to formaldehyde of 1:2 to 1:0.2, a molar ratio of methanol to methyl propionate of 1:1 to 5:1, a reaction temperature of 320 to 400° C., a reaction gauge pressure of 0 to 1 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.3 to 2.5 h -1 .

13. A catalytic material, characterized in that: The catalyst material is a zirconium silicon molecular sieve containing zirconium, silicon, oxygen and alkali metal elements. The catalyst material is characterized by XPS. 5 / 2 The central value of the binding energy of the zirconium spectrum peak is located at 182.4±0.4 eV. The catalytic material is characterized by pyridine infrared spectroscopy, and the acid content is less than 40 μmol / g at 150°C and less than 200 μmol / g at 50°C.

14. The catalytic material according to claim 13, characterized in that The alkali metal element is selected from one or more of lithium, sodium, potassium, rubidium and cesium.

15. The catalytic material according to claim 13, characterized in that The molar ratio of the alkali metal element to the silicon element in the zirconium silicon molecular sieve is (0.001-0.1):1, preferably (0.005-0.08):1, further preferably (0.005-0.06):1, more preferably (0.008-0.05):1, and most preferably (0.01-0.03):

1.

16. The catalytic material according to claim 15, characterized in that The zirconium-silicon molecular sieve has a molar ratio of zirconium to silicon of (0.001-0.05):1, preferably (0.004-0.03):1, further preferably (0.006-0.02):1, and more preferably (0.008-0.015):

1.

17. The catalytic material according to claim 13, characterized in that The zirconium silicate molecular sieve has a skeleton structure selected from at least one crystalline structure of MFI, MEL, MWW, BEA, MOR, and SVR structure molecular sieves; or the zirconium silicate molecular sieve is selected from at least one amorphous structure of MCM-41, MCM-48, and SBA-15 structure molecular sieves.

18. The catalytic material according to claim 13, characterized in that The zirconium silicate molecular sieve was characterized by NMR silicon spectrum, Q 4 With Q 3 The ratio of the signal peak height is greater than 100, where Q 4 (-113ppm) represents Si(OSi)4 species, Q 3 (-103ppm) represents Si(OSi)3(OH) species.

19. The catalytic material according to claim 18, characterized in that The Q 4 With Q 3 The ratio of the signal peak heights is greater than 150, preferably greater than 200, further preferably greater than 250, and more preferably greater than 300.

20. The catalytic material according to claim 13, characterized in that The zirconium silicate molecular sieve was characterized by NMR silicon spectrum, and there was no Q 3 The signal peak appears, Q 3 (-103ppm) represents Si(OSi)3(OH) species.

21. The catalytic material according to claim 13, characterized in that The zirconium silicate molecular sieve has a multi-level pore structure, containing micropores and at least one mesopore and / or macropore. The micropore diameter is less than 2nm, the mesopore diameter is 2-50nm, and the macropore diameter is greater than 50nm.

22. The method for preparing the catalytic material according to any one of claims 13 to 21, characterized in that: The preparation method comprises mixing zirconium silicon molecular sieve as raw materials with hydroxide or salt of alkali metal in the presence of an optionally added solvent, and then drying and roasting; the mixing treatment method adopts one or more of impregnation method, ion exchange method, spraying method, solid phase ion exchange method and grinding method, wherein the preferred mixing treatment method is grinding method; the mixing treatment is carried out for 5-120 minutes at a temperature of 20-150°C and an absolute pressure of 10-100KPa.

23. The preparation method according to claim 22, wherein: The zirconium silicate molecular sieve used as raw material has a skeleton structure selected from at least one crystalline structure including MFI, MEL, MWW, BEA, MOR, and SVR structure molecular sieves; or the zirconium silicate molecular sieve used as raw material has an amorphous structure selected from at least one amorphous structure including MCM-41, MCM-48, and SBA-15 structure molecular sieves.

24. The preparation method according to claim 22, wherein: The zirconium silicon molecular sieve as a raw material is obtained by a hydrothermal synthesis method.

25. The preparation method according to claim 22, wherein: The zirconium-silicon molecular sieve used as the raw material has a molar ratio of zirconium to silicon of (0.001-0.05):1, preferably (0.004-0.03):1, further preferably (0.006-0.02):1, and more preferably (0.008-0.015):

1.

26. The preparation method according to claim 22, wherein: The alkali metal is selected from one or more of lithium, sodium, potassium, rubidium and cesium.

27. The preparation method according to claim 22, wherein: The alkali metal salt is selected from the group consisting of alkali metal hydrochlorides, hypochlorites, chlorites, metachlorites, perchlorates, nitrates, sulfates, bisulfates, sulfites, bisulfites, phosphates, hydrogen phosphates, dihydrogen phosphates, high phosphates, metaphosphates, phosphites, hypophosphites, carboxylates, pyrophosphates, C1-C 20 One or more of the carboxylates.

28. The preparation method according to claim 22, wherein: The hydroxide of the alkali metal is cesium hydroxide, and the salt of the alkali metal is one or more of cesium nitrate, cesium carbonate, cesium bicarbonate, and cesium acetate.

29. The preparation method according to claim 22, wherein: The molar ratio of the raw materials zirconium silicon molecular sieve, alkali metal hydroxide or salt, and solvent is 1: (0.001-0.1): (0-10), wherein the raw material zirconium silicon molecular sieve is calculated as SiO2, and the alkali metal hydroxide or salt is calculated as alkali metal.

30. The preparation method according to claim 22, wherein: The molar ratio of the zirconium silicon molecular sieve as a raw material to the solvent is 1: (0-10) in terms of SiO2, preferably 1: (1-8), and more preferably 1: (1.5-6), more preferably 1:(1.5-4).

31. The preparation method according to claim 22, wherein: The mixing treatment is carried out at 25-100° C., preferably 30-70° C., and an absolute pressure of 20-80 KPa, preferably 30-50 KPa, for 5-60 min, preferably 10-30 min.

32. The preparation method according to claim 22, wherein: The drying is carried out at 60-150° C. for 0.5-24 h; and the calcining is carried out at 250-700° C. for 0.5-24 h.

33. The preparation method according to claim 22, further comprising a step of obtaining a multi-level porous structure by the participation of a silane compound.

34. A catalyst comprising a zirconium silicon molecular sieve, the zirconium silicon molecular sieve containing zirconium, silicon, oxygen and alkali metal elements, characterized by XPS, the Zr3d 5 / 2 The central value of the zirconium spectrum peak binding energy is located at 182.4±0.4 eV. The zirconium silicon molecular sieve is characterized by pyridine infrared. The acid content at 150°C is less than 40 μmol / g, and the acid content at 50°C is less than 200 μmol / g. The zirconium silicon molecular sieve is characterized by NMR silicon spectrum. Q 4 With Q 3 The ratio of the signal peak height is greater than 100, where Q 4 (-113ppm) represents Si(OSi)4 species, Q 3 (-103ppm) represents Si(OSi)3(OH) species; the weight ratio of the zirconium silicon molecular sieve to the catalyst is 5%-100%.

Citation Information

Patent Citations

  • Cs supported pure silicon molecular sieve catalyst, preparation method and applications thereof

    CN104258901A

  • Catalyst for preparing methyl acrylate and acrylic acid, and preparation method and application thereof

    CN106693941A